Karakteristik Fiber Metal Laminate Akibat Beban Impak Balistik Dari Peluru Kaliber 9 mm Full Metal Jacket (FMJ) - Fadly, Muhammad Syaiful; Purnowidodo, Anindito; Setyarini, Putu Hadi (Jurnal Rekayasa Mesin, 2021)
Estimated damage levels from ballistics impact zone provide valuable information to make bulletproof materials more effective. Therefore, this study aims to determine the impact of ballistics including hole shape, hole depth, macro, and microstructure on fiber metal laminate. The characteristics of ballistics impact for each configuration target is obtained from experiment and comparison based on simulations with finite element method. Test experiments used short-barreled fire guns at a distance of 5 meters with a normal attack angle based on the National Institute of Justice standard. Simulation with Johnson-Cook plasticity models for aluminum plate and orthotropic material model for kevlar/epoxy. The experiment and simulation results showed that the projectile is able to perforate the first layer (aluminum plate) and the second layer (Kevlar/epoxy) while the last layer (backplate) is deformed to form a bulge. The aluminum plate is perforated by the failure of petaling formation on the backside and spread of dimple fracture around the area of the petal which indicates ductile fracture while kevlar/epoxy is perforated by projectile with failure of fiber fracture on primary yarn, fiber pull-out, fiber stretching and fiber rupture.